Lycopene attenuates high glucose-mediated apoptosis in MPC5 podocytes by promoting autophagy via the PI3K/AKT signaling pathway - Wang, Qingfen (Exp Ther Med, 2020)
Podocyte injury serves an important role during the progression of diabetic nephropathy (DN), and lycopene (Lyc) may display a potential protective effect against DN progression. The effects of Lyc on high glucose (HG)-induced podocyte apoptosis and the underlying mechanisms are not completely understood; therefore, the present study aimed to investigate the effects of Lyc on HG-induced MPC5 podocyte apoptosis and the underlying mechanism. In the present study, MPC5 podocytes were exposed to HG and different doses of Lyc. MPC5 podocyte viability and apoptosis were assessed by performing the MTT assay and flow cytometry, respectively. To explore the effects of Lyc on the PI3K/AKT signaling pathway and autophagy, LY294002 (LY) and 3-methyladenine (3-MA) were used as PI3K and autophagy inhibitors, respectively. The expression levels of nephrin, podocin, apoptosis-related proteins (Bax, Bcl-2 and cleaved caspase-3), autophagy-related proteins [Beclin-1 and microtubule associated protein 1 light chain 3 (LC3)II/LC3I] and certain key proteins involved in the PI3K/AKT signaling pathway were measured via western blotting. The results suggested that Lyc reversed the inhibitory effect of HG on cell viability, and the protein expression levels of nephrin and podocin, as well as the promoting effect of HG on MPC5 podocyte apoptosis. In addition, under HG conditions, Lyc upregulated the phosphorylation levels of PI3K and AKT, and reduced HG- and LY-mediated MPC5 podocyte apoptosis. Moreover, Lyc further increased HG-induced protein expression levels of Beclin-1 and LC3II/LC3I, and attenuated LY-mediated inhibition of HG-induced MPC5 podocyte autophagy. In addition, the effects of Lyc on HG-mediated MPC5 podocyte apoptosis were alleviated by 3-MA. Therefore, the present study suggested that Lyc may protect against HG-induced MPC5 podocyte apoptosis by promoting autophagy activity via activation of the PI3K/AKT signaling pathway.